Semantic Connotation of Hadith and the Emergence of Arabic Schools of Grammar - S. A. Shittu; I. A. S. Adebolu (European Scientific Journal, ESJ, 2016)
Scholars focused the contributions of the Qur’ān to the evolution of Arabic Grammar, but few of them focused on the effect of prophetic tradition on the area. This paper, therefore, focuses on semantic connotation of prophetic traditions: “Guide your brother, he has gone astray” and “Divergent opinion of my followers is a blessing” These sayings of the prophet led to the evolution of Arabic grammatical studies and the establishment of its schools that enriched Arabic grammar. It opens with the grammarians’ contribution to the development of Arabic grammar such as Abul-Aswad Addu’alī (d.69 A.H), Seyyid ‘Ali b. Abī Talib, al-Khalīl ibn Ahmad al-Farāhidī and so on. Although, There were five major schools of Arabic grammar namely: al-Madhhab al-Basra, al-Madhhab al- Kūfa, alMadhhab al-Bagdād, al-Madhhab al- Andalusī and al-Madhhab al- Misrī but this paper, mainly focuses on the two prominent schools - Basran and Kūfan. It analyses the conflict of theory in Arabic grammar on some topics and other terms, grammatical debates between notable scholars of the two schools with their divergent opinions. The discussion ends with the justification of analogical deduction employed by the two schools in their analysis as a commendable exercise.